Learning from Beirut: From Modernism to Contemporary Architecture - Haddad, Elie G. (Enquiry The ARCC Journal for Architectural Research, 2008)
This paper will discuss the developments in architecture in Lebanon in the second half of the Twentieth century. Lebanon presents one of the interesting ‘laboratories' of the different tendencies and movements of this pastcentury, beginning with Modernism and its gradual assimilation, to Postmodernism and more current trends,in a context that presents a fertile field for experimentation. The questions of meaning, context, relations to place and tradition, have all played a part in the development ofarchitecture in Lebanon, without necessarily achieving their desired goals, especially in the current climate of globalization. The loss of material identity that many regions around the world have experienced is reflected in the case of Lebanon, exacerbated here by political and social conflicts. This paper argues that the attempts to reinject material forms with a measure of ‘communicative' symbols or forms fails in the end to answer to this perpetual desire for ‘identity'.